The Influence of Prenatal Alcohol and Tobacco Exposures on Offspring Mental Health and Substance Use Outcomes - Adema, Bereket Duko (Curtin University, 2022)
Using meta-analytical approaches and multi-generational birth cohort data extracted from the Raine Study, we found that prenatal alcohol and tobacco exposures were associated with increased risks of mental health and substance use problems in offspring. Taken together, there is sufficient evidence of harm observed in this thesis to warrant the precautionary principle, that there is no known safe level of prenatal alcohol and tobacco exposures and that such exposure should be minimized, if not avoided.